Implementation of Whistleblowing System in Fraud Prevention - Zahrah, Fatimah Az; Budiarti, Laeli (JAF (Journal of Accounting and Finance), 2024)
Fraud is an unlawful act that often harms companies or individuals. Corruption is the most common type of fraud in Indonesia. To address this, governments and companies have used various approaches, one of which is the whistleblowing system. Whistleblowing reports suspected fraud that has occurred or will occur within an organization. In this study, four auditors who work at the Inspectorate of Banyumas Regency were used as informants to see how whistleblowing helps prevent fraud. This research uses a case study approach and qualitative methods. Observation, interviews, and documentation are use to collect data. The results showed that although the regent's regulation has regulated whistleblowing in the Banyumas Regency Inspectorate, the system is still ineffective. The number of people using the complaint application and website is still low. In addition, after an audit is completed, no complaints have been proven. According to informants, whistleblowing is a specific complaint about violations or fraud that occurs in the workplace. However, the whistleblowing system at the Banyumas Regency Inspectorate is more focused on internal complaints, although they also receive complaints from external parties. This research provides an in-depth understanding of how whistleblowing is used in local government. This can be the basis for a better whistleblowing system and prevent fraud in the future.Keyword: Whistleblowing system; Fraud; Government.